Islamic Banking In Yemen In Light Of The Arab Uprising: An Empirical Study From Customer's Perspective - Abdullah Mohammed Ayedh,; Abdelghani Echchabi; Ameen Ahmed Alnahari (Asian Network for Scientific Information, 2024)
Non-Indexed Publication